2018
DOI: 10.1016/j.neuron.2017.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Normal CA1 Place Fields but Discoordinated Network Discharge in a Fmr1-Null Mouse Model of Fragile X Syndrome

Abstract: Silence of FMR1 causes loss of fragile X mental retardation protein (FMRP) and dysregulated translation at synapses, resulting in the intellectual disability and autistic symptoms of fragile X syndrome (FXS). Synaptic dysfunction hypotheses for how intellectual disabilities like cognitive inflexibility arise in FXS predict impaired neural coding in the absence of FMRP. We tested the prediction by comparing hippocampus place cells in wild-type and FXS-model mice. Experience-driven CA1 synaptic function and syna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
81
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 93 publications
14
81
3
Order By: Relevance
“…We examined several published datasets of extracellular recordings in hippocampal areas CA1 and CA3 during open field exploratory foraging. The following datasets were included in the analysis: two CA1 sessions from a teleportation experiment reported in Jezek, Henriksen, Treves, Moser, and Moser (), five CA1 sessions recorded in the Buzsaki lab (Mizuseki et al, 2013; Mizuseki et al, ; Mizuseki, Sirota, Pastalkova, & Buzsaki, ) (specifically session ec14.215, ec14.277, ec14.333, ec14.260, and ec15.047 from the openly available hc‐3 dataset), 16 CA1 sessions from wild‐type mice, and 16 CA1 sessions from Fmr1‐null mice recorded from Sparks, Talbot, Dvorak, and Fenton (), Talbot et al (), and Dvorak, Radwan, Sparks, Talbot, and Fenton (), also taken from the openly available hc‐16 dataset, 28 CA1 sessions in three rats from a remapping experiment reported in Schlesiger et al () and Schlesiger et al () and, finally, 178 CA3 sessions from seven rats in 11 rooms reported in Alme et al (). Details about the recordings and the experimental settings can be found in the respective references.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We examined several published datasets of extracellular recordings in hippocampal areas CA1 and CA3 during open field exploratory foraging. The following datasets were included in the analysis: two CA1 sessions from a teleportation experiment reported in Jezek, Henriksen, Treves, Moser, and Moser (), five CA1 sessions recorded in the Buzsaki lab (Mizuseki et al, 2013; Mizuseki et al, ; Mizuseki, Sirota, Pastalkova, & Buzsaki, ) (specifically session ec14.215, ec14.277, ec14.333, ec14.260, and ec15.047 from the openly available hc‐3 dataset), 16 CA1 sessions from wild‐type mice, and 16 CA1 sessions from Fmr1‐null mice recorded from Sparks, Talbot, Dvorak, and Fenton (), Talbot et al (), and Dvorak, Radwan, Sparks, Talbot, and Fenton (), also taken from the openly available hc‐16 dataset, 28 CA1 sessions in three rats from a remapping experiment reported in Schlesiger et al () and Schlesiger et al () and, finally, 178 CA3 sessions from seven rats in 11 rooms reported in Alme et al (). Details about the recordings and the experimental settings can be found in the respective references.…”
Section: Resultsmentioning
confidence: 99%
“…Fmr1‐null mice are used as a model for fragile X syndrome, exhibiting symptoms of intellectual disability such as cognitive inflexibility. Talbot et al ()) report that, although these mice place fields are no different than wild‐type, the timing of CA1 spikes are somewhat less organized by the phase of theta in the knockout mice than the wild type and also the phase‐frequency discharge probabilities of the place cells appear to be less coordinated in the knockout mice than the wild type. This led us to ask whether the phase‐distance relationship is disrupted in Fmr1‐null mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations